Aspirin‐exacerbated respiratory disease: longitudinal assessment of a large cohort and implications of diagnostic delay. Issue 4 (27th February 2020) - Kshirsagar, Rijul S.; Chou, David W.; Wei, Julia; Liang, Jonathan
Abstract : Background: Aspirin‐exacerbated respiratory disease (AERD) refers to the combination of asthma, chronic rhinosinusitis with nasal polyposis (CRSwNP), and acute respiratory tract reactions to ingestion of aspirin and nonsteroidal anti‐inflammatory drugs (NSAIDs). There have been no in the literature investigating diagnostic delay in AERD. We aimed to investigate whether delay of diagnosis of AERD is associated with poorer clinical outcomes as well as to characterize the role of specialty evaluation in diagnosis. Methods: We conducted a retrospective observational study of 254 subjects with incident AERD diagnoses between 2009 and 2016 among Kaiser Permanente Northern California (KPNC) members. Descriptive and bivariate statistics were employed to analyze clinical characteristics and outcomes of AERD subjects with and without delay in diagnosis (defined as 1 year or greater from symptom onset to diagnosis). Results: Of the 254 patients in the AERD cohort, 24.4% had a delayed diagnosis. Patients with allergies were significantly less likely to have a delay in diagnosis ( p < 0.01). Patients with a delay in diagnosis were more likely to have 2 or more courses of systemic steroids ( p = 0.04). Allergists, otolaryngologists, and primary care physicians diagnosed 56%, 36%, and 8% of patients, respectively. There was no association between provider specialty at time of diagnosis and delay in diagnosis ( p = 0.22). Conclusion: A substantial proportion of AERD patients have a diagnostic delay. Patients with allergies have a lower risk for this delay. This study is the first to describe diagnostic delay in AERD patients.